Modality in Makkan Arabic: The Interaction Between Modals and Aspect - Abusulaiman, Jumanah (Université d'Ottawa / University of Ottawa, 2019)
This dissertation explores the interaction between modality and aspect in Makkan Arabic (MA). There is some consensus in the semantic literature regarding the treatment of modal expressions that may obtain various ﬂavours, such as epistemic, deontic, bouletic, ability, necessity or teleological. These various modal ﬂavours can be captured by a uniﬁed lexical entry, and are identiﬁed by contextual factors Kratzer (1977, 1981, 1991, 2012). There is some debate regarding the structural location of modal elements, some of which have been argued to be high (the case of epistemic modals) and others low (the case of root modals) (e.g. Cinque (1999)). The relative scope of modals has been subject of much recent work on modality, in particular in relation to their interaction with temporal categories such as aspect. This thesis investigates this topic on the basis of novel data from MA. I observe that the ﬂavour of modality can change depending on how it is inﬂected with different types of aspect in MA. This observation is in line of Hacquard; Hacquard; Hacquard’s (2006; 2009; 2014) proposal for French and Italian. In MA, when the root modal \gdr\ “can” is inﬂected with the perfective, the combination yields entailments that have come to be known in the literature as ‘actuality entailments’ (AEs) (see Bhatt (1999, 2006)). In this case, the speaker gives rise to the inference that the proposition expressed by the complement holds in the actual world (instead of merely in some possible but not actual world). My thesis integrates the case of \gdr\ to current cross-linguistic debates on this topic. Building on Hacquard’s work, I argue that AEs are generated when perfective aspect scopes over root modals. Perfective aspect links events to the actual world. Imperfective aspect scoping over the modal fails to generate AEs. My thesis ex- ii tends the investigation of AEs to non-perfective cases. I argue that in addition to the contrast between perfective and imperfective, MA also distinguishes perfect aspect (e.g. an auxiliary plus a modal participle like gaadir). I suggest that the perfect in MA has several shapes, including the choice between two auxiliaries: kaan and saar. I link the different shapes of the perfect to the different types of interpretation identiﬁed by Portner (2000, 2003) for the English perfect. I suggest that in MA, different forms of the perfect are linked to distinct interpretations (which in English are grouped together under one form). In addition I show that, contrary to what has been argued by Hacquard for French, the perfect in MA can give rise to AEs in the case of the saar auxiliary. I develop an analysis of the saar perfect that is inspired by Hacquard’s proposal for perfective: in the case of saar, contrary to kaan, the perfect links the eventuality to the actual world. While the discussion of AEs in relation to the modal \gdr\ are linked to the proposal that aspect scopes over the modal, I also examine the case of a modal expression that scopes over aspect: qad “might”. I show that in spite of the fact that aspect scopes below the modal, the contrast between perfective and imperfective in the embedded clause can still give rise to differences in the generation of AEs. This case is interesting because much previous literature on AEs has focused on languages in which aspect scopes over the modal. MA qad provides an example where the modal scopes over aspect, and it is still the case that AEs appear to be generated. In spite of the structural differences with \gdr\, my analysis of qad builds on Hacquard’s proposal for AEs with the perfective, appealing to her proposal for the ‘preservation of event description’ to account for the fact that properties of eventualities can remain stable across worlds. The structure of the thesis is as follows: Chapter 1 provides an introduction to the empirical domain, situating aspect and modality in the description of MA; in addition it iii provides an introduction to key theoretical concepts to be used in later chapters. Chapter 2 discusses AEs in the case of the root modal \gdr\, comparing perfective and imperfective. Chapter 3 extends the discussion of the modal to examples with the perfect, distinguishing between the kaan- and saar- perfects. Chapter 4 investigates the behaviour of qad and its interaction with perfective and imperfective complements. Chapter 5 offers a brief summary and concluding remarks.
Keywords: Actuality entailment; Actuality entailment in Makkan Arabic; Semantics of Makkan Arabic modals; Semantics of Makkan Arabic aspectual system; Actuality entailment with root modals; Actuality entailment with epistemic modals; Actuality entailment with the perfect; Interaction between root modals and perfective aspect; Interaction between root modals and perfect aspect; Interaction between epistemic modals and the perfective; The Makkan Arabic perfect; Makkan Arabic aspectual system